HANDLING OF OFFICE MEETINGS AT THE MADIUN CITY LIBRARY AND ARCHIVE SERVICES - Kartikasari, Elly; Prihatinta, Triana; Hastuti, Farida Tri (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2025)
Meetings are a means that make it easier for companies or government agencies to discuss, exchange ideas, and discuss problems to reach decisions. In order for the meeting to run smoothly, good preparation is needed so that there are no obstacles during its implementation. The aim of writing this Final Assignment is to find out the stages of preparation for holding meetings at the Madiun City Library and Archive Services by using indicators of the stages of preparation for holding meetings, namely making meeting invitation letters, preparing meeting rooms, stationery, meeting equipment, accommodation, consumption (snacks), and health. The research method used is descriptive-qualitative, with data obtained through interviews, observation, and documentation. The informants used to collect data consisted of one head of general and finance sub-division and two TU secretariat staff. The results of this research show that the preparation stages for holding meetings at the Madiun City Library and Archive Services have met all indicators, namely making meeting invitation letters, preparing meeting rooms, stationery, meeting equipment, accommodation, consumption (snacks), and health, but from the indicators The health room is currently still combined with the lactation room.